2011
DOI: 10.1039/c1dt10177c
|View full text |Cite
|
Sign up to set email alerts
|

Selective colorimetric and fluorometric sensing of Cu(ii) by iminocoumarin derivative in aqueous buffer

Abstract: A new iminocoumarin based receptor L (C(27)H(26)N(4)OS) is synthesized with pyridyl and benzothiazolyl functionality. Synthesis of L is easy and it is isolated in good yield. L shows a selective and distinct color change from yellow to orange with Cu(2+) over Li(+), Na(+), Ca(2+), Mg(2+), Cr(2+), Mn(2+), Fe(2+), Co(2+), Ni(2+), Cu(2+), Zn(2+), Cd(2+), Pb(2+), and Ag(+) whereas a slight change in color is also observed in the case of Hg(2+) but L shows selective fluorescent quenching only in the presence of Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 63 publications
(3 reference statements)
0
24
0
Order By: Relevance
“…Iminocoumarin is a subclass of coumarin family [23], and very few reports are available in the literature describing the optical properties of iminocoumarins [24][25][26]. The reported iminocoumarin derivatives bear an electron-releasing group in the 7-position and an electron-acceptor group in the 3-position, a choice probably justified by the fact that this substitution pattern leads to enhanced absorption and fluorescence efficiency in the closely related coumarin series.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Iminocoumarin is a subclass of coumarin family [23], and very few reports are available in the literature describing the optical properties of iminocoumarins [24][25][26]. The reported iminocoumarin derivatives bear an electron-releasing group in the 7-position and an electron-acceptor group in the 3-position, a choice probably justified by the fact that this substitution pattern leads to enhanced absorption and fluorescence efficiency in the closely related coumarin series.…”
Section: Introductionmentioning
confidence: 94%
“…In the known iminocoumarins, the electron donors are N,N-dialkyl groups at 7 position and electron acceptors like benzothiazole or benzimidazole or cyano group at 3-position which enhance the fluorescence efficiency. The iminocoumarin derived fluorophores are known for their high fluorescence ability and efficient quantum yield and hence are used for metal sensors [9,26], biological system [27], pH sensor [28] and lasers [24]. The attachment of an ester or amide group in the 3-position leads to a dye with interesting lasing properties and high sensitivity to solvent effects [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in terms of practicability, the fluorophore indicators are generally immobilized in solid matrices for the purpose of obtaining optical Hg 2+ sensors with stability and long-term lifetime. Several optical Hg 2+ indicators were supported in swelling polymer matrix [21], but their long-term sustainability was not satisfactory as a result of variation in illumination, temperature, pressure, environmental pH, etc. Therefore, the incorporation of a fluorophore indicator with an inorganic matrix should be an effective approach for obtaining durable solid Hg 2+ chemosensor with high stability and environmental compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a number of fluorophores were synthesized to selectively detect highly toxic Hg 2+ in aqueous solution for meeting the environmental requirement [17][18][19][20]. However, the determination of Hg 2+ in a liquid circumstance suffers from difficulties of real-time and real-space measurements as well as complicated operation, which cannot be used with practical manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of the copper ions is unregulated, it can catalyze the production of reactive oxygen species which will damage biomolecules and thus can exhibit its role in oxidative stress and neurodegenerative disorders [3][4][5][6][7][8][9]. Therefore the researchers put considerable efforts in the design and development of fluorescent chemosensors, some of which are usable even in cellular imaging besides providing sensitive and selective detection toward Cu 2+ [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A number of molecular receptors reported in the literature suffer from poor water solubility, high detection limit and cytotoxicity toward normal cells [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%